Correlation between Hepatic Vein Wave form Changes on Doppler Ultrasound and the Severity of Diseases in Cirrhotic Patients (Journal of Medicine, 2021)
Background: Cirrhosis is a common problem and is a leading cause of chronic liver disease. Early diagnosis with assessment of severity of diseases may help prevent the associated complications and patients’ sufferings. Now a days Hepatic venous Doppler can be a tool for diagnosis of cirrhosis and to assess correlation between waveform changes and severity of diseases.Objective: The purposes of this study was to determine the significance of hepatic vein waveform changes on doppler ultrasound in cirrhotic patients and to correlate with liver dysfunction.Materials and methods: This study was carried out in the department of Radiology and Imaging of Enam Medical College and Hospital during January 2017 to May 2018. Doppler waveforms were obtained from right hepatic vein in all the cases and classified as triphasic, biphasic and monophasic. Waveform comparisons were made among patients with differing grades of cirrhosis. Child- Pugh class was used to assess severity of cirrhosis. Doppler sonography was done in 80 patients suspecting of having liver cirrhosis. Data on clinical findings, B mode sonographic findings and hepatic vein doppler ultrasound findings were collected and documented in structured forms. Analysis was done using SPSS - 20.Results: Total of 80 patients who met the inclusion criteria are included in the study with mean age of 45.37±7.64 (range 25-75) years. Among these 57 (71%) were males while 23(29%) were females. On the basis of hepatic function 25 (31%) patients presented in Child-Pugh Class A, 31(39%) with Class B and 24(30%) patients had Class C. Hepatic venous waveform was triphasic in 22 (27.5%), biphasic in 28(35%), and monophasic in 30 (37.5%) cases. Our study revealed 88% (21) of Child- Pugh Class C, 23% (7) of Class B and 8% (2) of class A patients had monophasic HV waveform. The hepatic venous waveform progressively changed from triphasic to biphasic to monophasic with advancing grade of cirrhosis. The relationship of these waveforms change had significant relation with hepatic dysfunction (p < 0.022).Conclusion: Hepatic vein wave form changes reflects the change in hepatic circulation associated with progression of liver cirrhosis. It can be used as a new parameter in the assessment of severity of liver cirrhosis. Thus, alteration in hepatic venous blood flow pattern on doppler ultrasound can be a useful noninvasive tool for evaluating diseases severity in patients with cirrhosis.J MEDICINE 2021; 22: 100-106